2010
DOI: 10.5424/sjar/201008s1-1223
|View full text |Cite
|
Sign up to set email alerts
|

In vitro interaction studies between Glomus intraradices and Armillaria mellea in vines

Abstract: An interaction study was performed with mycorrhizal plants of the grapevine rootstock Richter 110 (Vitis berlandieri Planch × Vitis rupestris Scheele) and the root pathogenic fungus Armillaria mellea (Vahl:Fr.) P. Kumm using an autotrophic in vitro culture system. Micropropagated plantlets were transferred to Petri plates with MSR medium lacking sugar and vitamins. Inocula of Glomus intraradices (BEG 72) and of Armillaria mellea obtained from a root organ culture and from a mycelium colony grown in malt agar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Using an in vitro system to study the interaction between white root rot infection caused by A. mellea and Glomus intraradices in the grapevine rootstock 110 Richter, Nogales et al (2010) showed a decrease in disease symptoms in mycorrhizal plants, confirming that the root colonization by a mycorrhizal fungus increased tolerance to white root rot, as reported in vineyard trials with mycorrhizal plants conducted by the same authors (Camprubi et al, 2008;Nogales et al, 2009). The AMF Glomus mosseae lowered mortality by Fusarium in basil (Ocimum basilicum L.), a plant species from the same family as lavender, and that effect was not related to P contents, which were similar in non-mycorrhizal and mycorrhizal plants (Toussaint et al, 2008).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Using an in vitro system to study the interaction between white root rot infection caused by A. mellea and Glomus intraradices in the grapevine rootstock 110 Richter, Nogales et al (2010) showed a decrease in disease symptoms in mycorrhizal plants, confirming that the root colonization by a mycorrhizal fungus increased tolerance to white root rot, as reported in vineyard trials with mycorrhizal plants conducted by the same authors (Camprubi et al, 2008;Nogales et al, 2009). The AMF Glomus mosseae lowered mortality by Fusarium in basil (Ocimum basilicum L.), a plant species from the same family as lavender, and that effect was not related to P contents, which were similar in non-mycorrhizal and mycorrhizal plants (Toussaint et al, 2008).…”
Section: Discussionmentioning
confidence: 65%
“…Under such conditions, the root can be colonized by an AMF monoxenically grown on Agrobacterium rhizogenestransformed roots in a root organ culture (ROC) (Declerck et al, 1996). In our experiment, the procedure followed to obtain the tripartite association (lavender plant-AMF-root rot fungus) was basically the same described by Nogales et al (2010) for grapevine plants.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycorrhizae can influence tree susceptibility and tolerance to economically important root pathogens such as Heterobasidion spp. and Armillaria mellea, even in the absence of direct antagonism of the pathogen by the endophyte (Gonthier et al 2019;Nogales et al 2010). Mycorrhizae are well recognized for their positive influence on tree growth and health so may antagonise pathogens via plant-mediated responses or ecologically through inhabiting the same niche, as is seen in other endophytes.…”
Section: Examples Of Tree Endophytes As Bcasmentioning
confidence: 99%
“…Furthermore, the conventional assays are extremely slow: preparation of woody inocula usually takes 3 to 6 months, the host plants require years to establish prior to inoculation, and then assessment of disease often lasts several years (Cleary et al, 2013;Morrison, 2004;Shaw, MacKenzie, Toes, & Hood, 1981;Solla et al, 2011). Inoculation assays using alternative hosts or other types of inocula such as rhizomorphs or wood chips (Holdenrieder, 1987;Pellegrini et al, 2014;Perez-Sierra & Gorton, 2005) are not well established and whilst the available in vitro assays are useful in that they are faster (Baumgartner, Bhat, & Fujiyoshi, 2010;Baumgartner, Fujiyoshi, Browne, Leslie, & Kluepfel, 2013;Nogales, Camprubí, Estaún, Marfà, & Calvet, 2010), they involve the preparation of tissue cultured material and substantial microscopy and molecular work. For these reasons, a faster inoculation assay that could be conducted under controlled conditions requires limited preparation and permits a simple assessment of infection would be desirable.…”
Section: Introductionmentioning
confidence: 99%